2016
DOI: 10.1371/journal.pone.0161564
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Traditional Chinese Exercise in Patients with Chronic Obstructive Pulmonary Disease: A Meta-Analysis

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a major public health problem worldwide. However, several studies that have assessed the role of traditional Chinese exercise in the management of this disease include broad variations in sample sizes and results. Therefore, this meta-analysis was conducted to assess the effects of traditional Chinese exercise on patients with COPD.MethodsTwo investigators independently identified and extracted data from selected articles. A computerized search of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…In previous systematic reviews of traditional Chinese exercise, including tai chi and qigong, for patients with COPD, improvements were found in FEV 1 and FEV 1 % predicted. [52][53][54] Tai chi exercise requires coordination of breathing and movement, strengthens respiratory muscles, and reduces pulmonary residual volume. 55 In our program, traditional 24-form tai chi was modified to a simple sixform version, keeping the essence of breathing control, taking patient exercise capacity into consideration, and maintaing training in balance and flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…In previous systematic reviews of traditional Chinese exercise, including tai chi and qigong, for patients with COPD, improvements were found in FEV 1 and FEV 1 % predicted. [52][53][54] Tai chi exercise requires coordination of breathing and movement, strengthens respiratory muscles, and reduces pulmonary residual volume. 55 In our program, traditional 24-form tai chi was modified to a simple sixform version, keeping the essence of breathing control, taking patient exercise capacity into consideration, and maintaing training in balance and flexibility.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The discrepancy between these results and ours may be attributed to different disease conditions of the patients and extent of clinical supervision in the rehabilitation program. However, traditional Chinese fitness exercises can significantly improve the pulmonary function of patients with stable COPD, 16 such as an intervention program that included 4 days of exercise at home and 3 days of exercise at the hospital. 17 The results suggested that long-term home-based traditional Chinese fitness exercises combined with clinical guidance can potentially improve lung function in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that exercise interventions for pulmonary function had different results (improved or not), 16 19 and the inconsistent results may be attributed to a range of factors, including the variations in patients’ health conditions, the extent of provided clinical supervision, and the amount of time dedicated to the intervention. However, different exercise programs for functional exercise capacity and quality of life of patients with COPD have consistent improvement results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that pulmonary function improved after traditional Chinese health exercise, whereas pursed lip breathing, abdominal breathing, and walking did not improve significantly [ 38 ]. A recent meta-analysis further confirmed the effects of traditional Chinese health exercise in COPD patients [ 40 ]. This may be explained by the fact that traditional Chinese exercise not only includes respiratory exercise, but also operates in tandem with upper and lower limb exercise to further strengthen the role of auxiliary respiratory muscles.…”
Section: Discussionmentioning
confidence: 90%